Analysis of interactions between IT and organisational resources in a manufacturing organisation using cross-impact analysis. Issue 4 (11th July 2016) - Ceric, Arnela
Abstract : Purpose: – The purpose of this paper is to contribute to a growing body of research on the applicability of resource-based theory (RBT) to the information systems (IS) area. In particular, the paper provides an understanding of the IS value creation process, and strategies for managing it by demonstrating the application of cross-impact analysis. Design/methodology/approach: – RBT and systems theory are adopted as a theoretical framework in this study. Cross-impact analysis is used as a method for investigating interactions among elements of an IS value creation system. These elements were identified through 22 semi-structured interviews with organisational stakeholders, and assessed in terms of direction and strength of their interactions, and depicted in a coordinate system. Findings: – The result of the analysis is a meaningful classification of elements in an IS value creation system as: levers, indicators, identities, buffers or trends, based on their position in the system. The results provide additional clarity and insights into the relationships between IS and organisational resources and their effect on IS value. Research limitations/implications: – The research findings have important implications for researchers and managers in terms of understanding the impact of interactions among IS and organisational resources on formulating successful strategies for managing the IS value creation system. Originality/value: – This study explores interactions among IS/information technology resources and organisational resources by using cross-impact analysis. It shows that interactions among the identified resources do have a major influence on the overall IS value creation system.